Cerita Si Kuncung: Membaca Relasi Kuasa dalam Majalah Anak-anak Indonesia - Atika S. Hadi (Diponegoro University, 2018)
Si Kuncung is the first kid's magazine that officially accepted as a national kid's magazine by the Indonesian government in the era of President Soeharto. Aside from being a media for education and culture, the government also helped Si Kuncung's publications, especially in marketing and financing. The relationship between the publishers and the government expanded the deployment of Kuncungand strengthened its position in the national children's reading materials. However, on the other hand, Si Kuncung who dissolved in the leadership of power also faded along with the collapse of the New Order era.